Serum CA 125 combined with transvaginal ultrasonography for ovarian cancer screening - Roupa, Zoi; Faros, Efthimios; Tzavelas, George; Kotrotsiou, Evangelia; Sotiropoulou, Penelope; Karanikola, Evridiki; Skifta, Evdoxia; Ardavanis, Alexandros S.; Raftopoulos, Vasilios (My University, 2004)
Background: The aim of this study was to evaluate the combination of serum CA125 and Transvaginal Ultra Sonography (TVUS) score, as a screening procedure for ovarian cancer in premenopausal and postmenopausal women. Patients and Methods: A retrospective case-control pilot study was conducted. The files of 120 women with ovarian neoplasia detected by TVUS and increased CA125 level, within the framework of a prevention program, were reviewed. The relationship between the above tests and epithelial malignancy was investigated using the SPSS-12 program for Windows. Results: The combination of CA125 value exceeding 30U/ml and a TVUS score ≥35 had a sensitivity of 81.7% and specificity of 100% in predicting ovarian cancer. Mathematical analysis of the logistic model of our variables revealed a mathematical model that can calculate the likelihood of ovarian cancer detection, by using a combination of CA125≥30U/ml and TVUS score≥35. Conclusion: By combining TVUS and CA125, an accurate prediction for the presence of ovarian cancer may be achieved. Further investigation in a larger population is warranted.
Keywords: Serum CA 125; Ultrasonography; Cancer